BIBLIOMETRIC ANALYSIS OF SCOPUS INDEXED JOURNALS OF THE SUPPLY CHAIN IN SMALL AND MEDIUM ENTERPRISE: 2015-2024 - Kaluku, Moh Ramdhan Arif; Sumiati; Rofiq, Ainur; Hadiwidjojo, Djumilah (Pesquisa operacional, 2025)
ABSTRACT The aim of this study is to investigate the field of supply chain (SC) in small and medium businesses (SME) over the past 10 years by means of a bibliometric analysis of papers released in Scopus-indexed journals. The approach applied is bibliometric analysis and scientific mapping. This study utilizes bibliographic data of indexed papers retrieved from the Scopus database. This work detects research clusters for topological analysis, identification of important research subjects, interrelations, and cooperation patterns using bibliometric techniques. According to the results, 804 papers were published between 2015 and 2024; a total of 12,109 citations were made to these papers, and with an average of 96.80 citations per year. With 2,293 authors from 72 countries having published works, co-authorship and international cooperation have grown. The leading publishing countries for SC in SME in Scopus-indexed journals include China, Indonesia, and India. This study solely covers papers from 2015 to 2024; we did not examine publications released prior to 2015. This study solely examined bibliographic data of publications; it did not examine the contents of papers, including titles, approaches, or other components. It also aids in identifying present areas of interest for research and possible paths of inquiry.